Corporates' monitoring costs of fair value disclosures in pre- versus post-IFRS7 era: Jordanian financial business evidence - Esraa Esam Alharasis; Manal Alidarous; Abeer F. Alkhwaldi; Hossam Haddad; Nidal Alramahi; Husni K. Al-Shattarat (Cogent Business & Management, 2023)
This study proposes a new auditing model that takes Fair Value Accounting (FVA) into account as a unique complexity and risk factor. It gives new empirical data on audit firm monitoring in Jordan over two periods: before and after the implementation of IFRS7 (pre- vs. post-IFRS7). The Ordinary Least Squares regression, which used 1470 firm-year observations from 2005 to 2018, reveals that post-IFRS7 positively impacts audit fees, whereas pre-IFRS7 has no effect. According to the change analysis, increasing Fair Value Disclosure (FVD) is the primary driver of rising audit expenses in the post-IFRS7 era (particularly for Level2 assets). An additional test using firms with and without FVDs corroborated these findings even more. The moderating influence of the presence of FVA on each pre-and post-IFRS7 and audit fees shows that the use of FVA is the primary cause of Jordan's high audit fees during the mandated FVA period. This research is the first to present fresh empirical evidence on audit firms monitoring expenses before and after FVD regulations using a sample from Jordan. The study's findings provide regulators with up-to-date practical information regarding adopting FVA. The outcomes help lawmakers monitor the audit profession and regulate FVA audit procedures.
Keywords: 650; audit fees; developing countries; fair value accounting; IFRS7; Jordan